A Cobalt‐Based Metal–Organic Framework as Cocatalyst on BiVO4 Photoanode for Enhanced Photoelectrochemical Water Oxidation. Issue 16 (19th July 2018) - Zhang, Wang; Li, Rui; Zhao, Xin; Chen, Zhong; Law, Adrian Wing‐Keung; Zhou, Kun
Abstract: A metal–organic framework (MOF)‐modified bismuth vanadate (BiVO4 ) photoanode is fabricated by an ultrathin sheet‐induced growth strategy, where ultrathin cobalt oxide sheets act as a metal source for the in situ synthesis of Co‐based MOF poly[Co2 (benzimidazole)4 ] (denoted [Co2 (bim)4 ]) nanoparticles on the surface of BiVO4 . [Co2 (bim)4 ] with small particle size and high dispersion can serve as a promising cocatalyst to accept holes transferred from BiVO4 and boost surface reaction kinetics for photoelectrochemical (PEC) water oxidation. The photocurrent density of a [Co2 (bim)4 ]‐modified BiVO4 photoanode can achieve 3.1 mA cm −2 under AM 1.5G illumination at 1.23 V versus the reversible hydrogen electrode (RHE), which is better than those of pristine and cobalt‐based inorganic materials‐modified BiVO4 photoanodes. [Co2 (bim)4 ], with porosity and abundant metal sites, exhibits a high surface charge‐separation efficiency (83 % at 1.2 V versus RHE), leading to the enhanced PEC activity. This work will bring new insight into the development of MOF materials as competent cocatalysts for PEC water splitting applications. Abstract : Grown inducing cocatalysis : Cobalt‐based metal–organic framework (MOF) nanoparticles were uniformly loaded on the surface of BiVO4 by an ultrathin sheet‐induced growth strategy. The Co‐based MOF, with small particle size and high dispersion, can act as a promising cocatalyst to boost surface reaction kinetics, leading to the enhanced water oxidation performance of the MOF‐modified BiVO4 photoanodes.